2021
DOI: 10.4102/sajpsychiatry.v27i0.1585
|View full text |Cite
|
Sign up to set email alerts
|

My sibling’s mental illness: An interpretative phenomenological analysis of experiences of having an adult sibling with a mental illness in semi-rural South Africa

Abstract: Background: When there is a lack of resources in the community to support deinstitutionalisation, the siblings of an individual with a mental illness are the ones who are the most affected and vulnerable. Nevertheless, sibling care work is still largely unacknowledged in the mental health sector in low- and middle-income countries.Aim: This article describes and interprets the lived experiences of ‘black’ isiXhosa-speaking individuals having a sibling with a mental illness, to shed light on how mental health p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It was like he is doing it for fun. (Young & Flannigan, 2021) Dependent on SOPEP's personal and social identity, their experiences of having an 'ill' sibling may vary. This may have an impact for SOPEP during adolescence and early adulthood on the sibling relationship (Graves et al, 2021), relationships with their parents (e.g., feeling abandoned) and their psychosocial functioning.…”
Section: Beliefs About Psychosismentioning
confidence: 99%
See 3 more Smart Citations
“…It was like he is doing it for fun. (Young & Flannigan, 2021) Dependent on SOPEP's personal and social identity, their experiences of having an 'ill' sibling may vary. This may have an impact for SOPEP during adolescence and early adulthood on the sibling relationship (Graves et al, 2021), relationships with their parents (e.g., feeling abandoned) and their psychosocial functioning.…”
Section: Beliefs About Psychosismentioning
confidence: 99%
“…When my parents die … I think (caregiving) would fall to me. (Dodge & Smith, 2019) 3.3.4 | Personality traits SOPEP expressed compassion, empathy and patience towards their sibling and wanting to provide a calming presence when socialising together (Al-Sawafi et al, 2021;Al Sawafi et al, 2022;Amaresha et al, 2019;Bishop & Greeff, 2015;Day & Petalas, 2020;Graves et al, 2020;Liu & Zhang, 2019;Park & Lee, 2017;Young & Flannigan, 2021). SOPEP desired patience when communicating with their siblings, mostly when they felt exhausted or frustrated by the sibling's behaviours (Amaresha et al, 2015;Kovacs et al, 2019).…”
Section: Family and Cultural Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…This view is supported by Park and Lee ( 2017 :97), who found that limited information is available about sibling caregivers because existing studies focus on other family relationships, such as those with parents, spouses and children. Besides the study by Young and Flanagan ( 2021 ), there is a paucity of literature regarding the experiences of siblings caring for their sisters or brothers in South Africa. To fill this knowledge gap, the purpose of this study was to describe family members’ experiences caring for a sibling with mental illness in Giyani.…”
Section: Introductionmentioning
confidence: 99%